Karakterisasi Bionanofiller Dari Limbah Padi Sebagai Alternatif Penguatan Pada Polimer Komposit - Eryani Eryani; Sri Aprilia; Farid Mulana (Jurnal Serambi Engineering, 2018)
Agricultural waste such as rice straw, rice husk and rice husk ash have not been utilized properly. This waste of agricultural produce can actually be used as an alternative to bionanofiller because it contains an excellent source of silica. The silica content contained in the rice waste when combined with the polymer matrix can produce composites having high thermal and mechanical properties. Characterization of bionanofiller from this rice waste is done by SEM, XRF, FTIR, XRD and particle density. The result of SEM analysis from this rice waste is feasible to be used as filler because it has size 1 μm. Likewise with the results of XRF analysis that rice waste contains a high enough silica component that is 80.6255% - 89.83%. FTIR test results also show that bionanoparticles from rice waste have the same content of silica. In the XRD analysis the best selective gain of rice waste is found in rice husk ash which is characteristic of amorp silica at a range of 2ϴ = 22. The largest density analysis of paddy waste was found in rice husk 0.0419 gr / cm , followed by rice straw by of 0.0417 gr / cm 3 and rice hulk ash 0.0407 g / cm 3